Seismic performance of a 3D full-scale high-ductility steel?concrete composite moment-resisting structure?Part I Design and testing procedure. - Braconi, A.
A multi-level pseudo-dynamic (PSD) seismic test programme was performed on a full-scale three-bay two-storey steel?concrete composite moment-resisting frame built with partially encased composite columns and partial-strength connections. The system was designed to provide strength and ductility for earthquake resistance with energy dissipation located in ductile components of beam-to-column joints including flexural yielding of beam end-plates and shear yielding of the column web panel zone. In addition, the response of the frame depending on the column base yielding was analysed. Firstly, the design of the test structure is presented in the paper, with particular emphasis on the ductile detailing of beam-to-column joints. Details of the construction of the test structure and the test set-up are also given. The paper then provides a description of the non-linear static and dynamic analytical studies that were carried out to preliminary assess the seismic performance of the test structure and establish a comprehensive multi-level PSD seismic test programme. The resulting test protocol included the application of a spectrum-compatible earthquake ground motion scaled to four different peak ground acceleration levels to reproduce an elastic response as well as serviceability, ultimate, and collapse limit state conditions, respectively. Severe damage to the building was finally induced by a cyclic test with stepwise increasing displacement amplitudes.
Keywords: Seismic design; Ductility; Steel?concrete composite frames; Partial-strength beam-to-column joints; Composite members; Pseudo-dynamic testing